TARI AMERTA SRI BUMI: REPRESENTASI UPACARA PERANG TIPAT DALAM MERDEKA BELAJAR-KAMPUS MERDEKA BERSAMA SANGGAR SENI PANCER LANGIIT - Ni Kadek Ary Apriyani; Ida Ayu Trisnawati; A.A Ketut Oka Adnyana (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2022)
This article is the result of research from the Amerta Sri Bumi Dance: Representation of the Tipat War Ceremony as a new dance creation symbolized as Purusa and Pradana as well as the depiction of Dewi Sri as the Goddess of fertility.This research focuses on the creative process and the form of the Amerta Sri Bumi Dance presentation. This research was structured based on postmodern theory, creativetheoryand the theory of group choreography elements by using qualitative research methods through interview techniques, literature study techniques and documentation techniques.Data analysis has shown that Amerta Sri Bumi Dance is either a welcome dance or an inspired creation of cultural attractions which are the hay hairier and more commonly known as the tipat wars and pillows that are in the Kapal village, Badung distric. By means of the concept of interpreting tipat and the pillows that lifted the essence by bringing together the two symbolic elements of the source of affluence, Purusa and Pradana, fertility, described as goddess Sri.The method employed in the creation of Amerta Sri Bumi dance is the langon method stemming from lontar Purwadigama that states that there are three concepts such as (1) concepts control called ungon, (2) concepts reinforcement called ingon, (3) concepts the mastery called angon.The Amerta Sri Bumi dance uses seven dancers, namely three women symbolized as Pradana, three men symbolized as Purusa. Then one woman as the character of Dewi Sri who wears a magnificent sling.